Influence Motivation Learning Students and Creativity Teachers on Results Learning Eyes Learning Education Citizenship Class VIII - Yuri Gagarin Tampubolon; Sanggam Magda Lasmaria Siahaan; Sepriandison Saragih (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
Teachers' efficacy towards the Learning outcomes f Civic Education Subjects for Class VIIIf Cinta Rakyat 2 Private Middle School, Pematangsiantar. This research is a quantitative study using a correlational method, which aims to examine the relationship and influence between the independent and dependent variables. The population in this study was all 70 eighth-grade students, with a total sampling technique, so that the entire population was sampled. The instruments used in this study were a student learning motivation questionnaire and a teacher creativity questionnaire, while learning outcome data were obtained from summative scores for the Civics subject. The data were analyzed using multiple linear regression analysis to test the simultaneous and partial influence between variables X, (student learning motivation) and X, (teacher creativity) n variable Y (learning outcomes). The results f the study showed that: (1) there is a positive and significant influence between student learning motivation n learning outcomes f Citizenship Education, (2) there is a positive and significant influence between teacher creativity n learning outcomes f Citizenship Education, and (3) simultaneously, student learning motivation and teacher creativity have a significant influence n learning outcomes f Citizenship Education. Thus, it can be concluded that the higher the student learning motivation and the more creative the teacher in implementing learning, the better the student learning utcomes in the subject f Citizenship Education